Teknik Penilaian Sikap Spritual dan Sosial dalam Pendidikan Karakter di Sekolah Dasar 08 Surau Gadang Nanggalo - Darmansyah, Darmansyah (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
Curriculum 2013 mandated that learning process in Elementary School should be carried out with an integrated thematic approach.Â Despite of it is being tested this year; the implementation of an integrated thematic learning model requires serious effort and creativity of teachers with various forms of new innovations. Context analysis conducted in the SD (Elementary School) 08 Surau Gadang Nanggalo Padang as objects and implementation of product testing research grant competition revealed that teachers understanding of the concept and implementation of assessment of spiritual and social attitudes have not been satisfied.Â Teachersâ inappropriate competence in the evaluation of spiritual and social attitudes had negative impact on the studentsâ achievement of first core competencies (KI1) and second core competencies (KI2) as they constitutes major focus in the character-based curriculum.Â Data of this study were collected by using interview and documentation; they were finally preceded through descriptive qualitative analysis. The results of this study reveal that there were four models of assessment that can be performed in the evaluation of spiritual attitudes and social attitudes namely (1) self evaluation, (2) observation of teachers, (3) peer assessment, and (4) daily journal.CopyrightÂ Â©Â 2014Â by Al-TalimÂ AllÂ rightÂ reservedDOI:Â 10.15548/jt.v21i1.67